Pengembangan Dan Validasi Metode Analisis Propanolol Hidroklorida Tablet Dengan Metode Absorbansi Dan Luas Daerah Di Bawah Kurva Secara Spektrofotometri Ultraviolet - Boy Chandra; Harrizul Rivai; Edwin Apriansyah (Jurnal Farmasi Higea, 2017)
The simple, accurate, sensitive and selective ultraviolet spectrophotometry has been developed and validated for analyzing of propanolol hydrochloride tablets with absorbance and area under curve method. These methods used solvent HCl 0.1 N with wavelength 288.60 nm, and the area under the curve measured at a wavelength of 248-302.80 nm. The calibration curve obtained in the concentration range of 8-16 µg/mL. With absorbance method showed results of the linear regression equation of y = - 0.1516+0.0502x  and value of r = 0.99993 and with the area under curve method showed results of the linear regression equation y  = –2.664+0.7657x  and value of r = 0.99973. The percentage of propanolol hydrochloride tablets with trademark of propanolol HCl absorbance method was 99.21 %  and with area under curve method it showed 101.24 %. The percentage levels of both samples fill the Indonesian Pharmacopoeia standards edition V which was 90–110 %. The average of percent recovery and RSD were obtained from both samples by absorbance and area under curve fill of validation parameters, ie 80-120 % and 1-2 % respectively. Statistical analysis showed that there was no significantly different between both of these method (sig.>0.05).